Cultural elements in the english textbook “Objective key” = Yếu tố văn hóa trong sách tiếng Anh “Objective key” - Nguyễn, Thị Thúy Ngân (2020)
Cultural elements in textbooks are one of the central research topics in English language teaching as culture and language relationship are highly intertwined and inseparable. However, in a large number of textbooks, culture is perceived to be fixed, quantifiable and unchangeable. Furthermore, cultural factors included in textbooks mostly serve the purpose of introducing and practicing language patterns. This fact-based approach of cultural learning has its own drawbacks since it seldom provides students opportunities to develop critical thinking or encourage reflection on their own lived experiences; as a result, students might not be able to develop “global cultural consciousness” (Kumaravadivelu, 2008) or “intercultural citizenship” (Byram, 2011) which has been defined as the desired learning outcome of the 21st century language learners. Adopting the semiotic framework by Weninger and Kiss (2013), along with both quantitative and qualitative methods, this study, therefore, aimed at examining how cultural elements are represented in the English textbook “Objective Key” and how text-image-task as the whole complex might trigger the different interpretations among students and encourage cultural learning. The study results reveal that the relationship between texts and images is highly indexical, and images incorporated in the textbook mostly serve as linguistic reinforcement or space fillers. Moreover, as pedagogical tasks are overwhelmingly intended for linguistic purpose, learners do not have many opportunities to reflect on learning content, which also implies that cultural elements in this textbook are treated merely as the medium for linguistic practice. These findings hence suggest that teacher’s adaptation is essential so that cultural learning content can be fully utilized, and culture learning will not be overshadowed by linguistic practice.